The ruptures in our rainbow: Reflections on teaching and learning during #RhodesMustFall - Hlathswayo, Mlamuli (Critical Studies in Teaching and Learning, 2023)
In this paper, I attempt to explore and theorizethe “ruptures”in our rainbow nation through foregrounding higher education in general and teaching and learning practices in particular. I rely on Morrow (2009),in particular his intellectual and philosophical contributions on epistemological accessto make two contributions. Firstly, Iarguethat the South African higher educationurgently needsto re-conceptualize the theoretical understanding of “access” beyond formal, simplistics notions. Secondly, I hope to show how an re-adoption of Morrow’sunderstanding of epistemological access can enable progressive engagements between academicsand students in both having respect for anda critical understanding of the different disciplinesand knowledge(s)in higher education.I suggest that a return toMorrow’s ideaof epistemological access will not only enable usto make the make the necessary “repairs”to ourrainbow nation but it will also enable usto better respond to the progressive and innovative calls in teaching and learningthat contemporary South African higher educationgreatly demands of us.